The Necessary Nation - Jusdanis, Gregory (Book collections on Project MUSE., 2008)
In this controversial look at nationalism, Gregory Jusdanis offers a sweeping defense of the nation as a protector of cultural difference and a catalyst for modernization. Since the end of the Cold War, the nation-state has undergone intense scrutiny among critics in the media and the academy. Many believe that civic nationalism may be fruitful but that cultural nationalism fosters xenophobia and backward thinking. Jusdanis, however, emphasizes the positive collaboration between nation-building and culture. Through a series of critical readings of multicultural, postcolonial, and globalization.